Mutation in Shigella flexneri Resulting in Loss of Ability to Penetrate HeLa Cells and Loss of Glycerol Kinase Activity - Kim, Rosalind (1974)
A colonial variant of a virulent Shigella flexneri 2a has lost both virulence and glycerol kinase activity. It also has several other altered characteristics: lowered ability to oxidize tricarboxylic acid cycle intermediates, increased electrophoretic mobility, and decreased sensitivity to sodium lauryl sulfate. Genetic analysis has revealed that the gene governing glycerol kinase activity in Shigella has a different chromosomal locus than that from Escherichia coli. Furthermore, transduction of the Shigella glycerol kinase gene (glp K) into the avirulent Shigella strain can restore the ability to penetrate HeLa cells, whereas the gene from E. coli cannot. About half of the glp K mutants lose this ability, and only about half of the revertants of an avirulent glp K mutant regain it. This indicates that more than one gene affects glycerol kinase activity in Shigella, only one of which is associated with penetration. Glycerol kinase activity is closely correlated with changes in electrophoretic mobility, but does not appear to have any relationship to sodium lauryl sulfate sensitivity nor to the oxidation of tricarboxylic acid cycle intermediates.